Is 21st Century Learning Need STEM Approach built into Physics Comics? - Maria Fatima Nareswari Mardi Utami; Mastuang Mastuang; Surya Haryandi (Jurnal Ilmiah Pendidikan Fisika, 2023)
This study aims to analyze the effectiveness of using comic teaching materials in physics learning, focusing on the topic of effort and energy. The background of this research is based on the need to improve the quality of physics learning and improve student learning outcomes. In Indonesia's education context, efforts continue to be made to improve STEM-based education (Science, Technology, Engineering, Mathematics) to keep up with the development of the 21st century. In the context of this research, comic teaching materials are used as a new alternative to overcome problems in physics learning. This research was conducted in one of the public high schools in Banjarmasin and used the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). Data were collected through student learning outcomes tests before and after using comic teaching materials. The results showed that this comic teaching material significantly increased student learning outcomes. Student scores increased from a low of 0.00 to 43.00 and a high of 18.50 to 80.50. This increase in learning outcomes test is included in the medium category. This research contributes to developing comic teaching materials as an effective and innovative learning media in physics learning. It is expected that the results of this study can be a reference for educators and curriculum developers in improving the quality of physics learning in Indonesia. In addition, this research also encourages further development and utilization of creative media in education to increase student motivation and interest in learning.